Pengaruh Literasi Keuagan dan Financial Technologi Terhadap Minat Mahasiswa Dalam Berinvestasi - Rosita Rosita; Jumawan Jasman; Asriany Asriany (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Financial literacy refers to the skills and measurements of objective information and individual knowledge related to personal financial management and decision making. The complexity of financial instruments and the development of information technology increase the interest of students in investing, the unit of analysis of which is the students of Muhammadiyah Palopo University. Primary data was obtained by distributing questionnaires, in which 82 respondents participated. The data analysis technique is multiple regression linear analysis. This study shows that financial literacy and financial technology influence investment interest. As for the financial technology variable, it does not have a significant effect on investment interest of Palopo Muhammadiyah University students. Keywords: Financial Literacy, Financial Technology, Investment Interest